Prevalence of Mental Effect of Workload on Nursing Staff - Latif Ahmad; Zahidullah; Sajid Ali; Shahan khan; Attaullah; Muhammad Sabir; Spogmay khan; Kamran khan; Sana Ullah; Aizaz khan (Journal of Health, Wellness and Community Research, 2026)
Background: Nursing workload is a multidimensional occupational exposure that can contribute to psychological strain and functional impairment, particularly in high-acuity hospital settings where staffing constraints and time pressure are common. Objective: To estimate the prevalence of workload-related mental health effects among hospital nurses and assess associations between perceived workload intensity and frequency of overwhelm, and between stress-related impacts on work performance and personal life. Methods: A quantitative cross-sectional observational study was conducted among 100 registered nurses at Saidu Group of Teaching Hospital, Saidu Sharif, Swat, Pakistan, over one month. Data were collected using a structured self-administered questionnaire assessing demographics, perceived workload intensity, frequency of feeling overwhelmed, self-reported workload-related mental health symptoms in the past month (fatigue, anxiety, burnout, depressive symptoms), workplace support and staffing adequacy, and functional impacts. Descriptive statistics summarized prevalence. Associations were tested using chi-square, with effect size quantified using Cramer’s V. Results: Most nurses reported workload overwhelm at least sometimes (72.0%), with 28.0% reporting frequent overwhelm (often/almost always). Perceived workload was rated as at least somewhat heavy by 63.0%. The most common workload-related mental health symptom was fatigue (50.0%), followed by anxiety (20.0%) and burnout (19.0%). Workload intensity was significantly associated with frequency of overwhelm (χ²(12)=35.23, p<0.001; Cramer’s V=0.34). Stress impact on work performance was significantly associated with stress impact on personal life (χ²(16)=45.80, p<0.001; Cramer’s V=0.34). Conclusion: Workload-related psychological strain is prevalent among hospital nurses and shows a clinically meaningful exposure–response gradient with perceived workload intensity, supporting the need for organizational interventions targeting staffing, workload management, and mental health support.